Macromedia Dreamweaver 8 : training from the source - Page, Khristine Annwn (Adobe Press, 2006)
Learn by doing! The lessons in this book guide you step-by-step through the creation of a project Web site, "Yoga Sangha." With Macromedia's official guide, you'll learn how to use the leading, best-selling Web editor and gain a thorough understanding of how you can use Dreamweaver 8 to effectively manage and maintain Web sites, develop sites that are accessible to a wide audience, and work in an environment that integrates visual and code editing. As you complete the tasks, you'll develop the skills and techniques that you need to create Web sites on your own. In addition to the basics of creating a Web page that incorporates text, graphics and tables, you'll learn about all that's new in Dreamweaver 8: visual authoring with XML data, advanced CSS support including a unified CSS panel and a style rendering toolbar, integration with the latest Web technologies and standards, and more. The companion CD-ROM contains all of the lesson files as well as a free trial version of Dreamweaver 8.